Evolusi Sistem Pendidikan di Indonesia: Sejarah dan Perkembangan Pendidikan di Indonesia - Muhammad Idris; Arismunandar; Ismail Tolla (UNIVERSITAS PGRI YOGYAKARTA, 2024)
Education in Indonesia has undergone significant changes throughout its history, influenced by various social, political, and cultural factors in each period. During the colonial era, the education system in Indonesia was designed to maintain colonial power, with a discriminatory structure that provided access to education only for the elite and a small number of indigenous people considered suitable for supporting colonial administration. However, educational figures such as Ki Hajar Dewantara sought to introduce a more inclusive education system based on local culture through the establishment of Taman Siswa. After Indonesia’s independence in 1945, the education system faced significant challenges, with the primary focus being on equalizing access to education and shaping the national character that accommodates social and cultural diversity. During the New Order period, the implementation of the nine-year compulsory education policy successfully increased access to education, yet it was still influenced by the goal of political stability and economic development driven by the authoritarian government. Following the 1998 Reformation, Indonesia introduced decentralization policies, granting local governments more autonomy in managing education, although disparities in education quality between urban and rural areas remain a major challenge. Additionally, in the era of globalization, Indonesian education faces new challenges in creating a more inclusive, high-quality, and relevant education system that meets current social and economic needs. Therefore, understanding the evolution of Indonesia's education system is essential not only to identify policy changes but also to explore the role of education in shaping national identity and supporting national development.